Activation of CXCL6/CXCR1/2 Axis Promotes the Growth and Metastasis of Osteosarcoma Cells in vitro and in vivo - Liu, Guangchen; An, Liping; Zhang, Hongmei; Du, Peige; Sheng, Yu (Frontiers in Pharmacology, 2019)
Osteosarcoma (OS) is a malignant primary bone tumor with high metastatic rate. C-X-C motif chemokine ligand 6 (CXCL6) and its receptor C-X-C motif chemokine receptor 1/2 (CXCR1/2) have been found to participate in the process of carcinogenesis. In this study, we evaluated the role of CXCL6/CXCR1/2 axis in proliferation and metastasis of OS cells. According to our results, the mRNA and protein expressions of CXCL6, CXCR1, and CXCR2 in multiple OS cell lines were determined. Treatment with exogenous CXCL6 for more than 72 h significantly promoted the proliferation of OS cells. Blocking the effect of endogenous CXCL6 restrained the migration, invasion and epithelial-mesenchymal transition (EMT) as evidenced by increased E-cadherin level, decreased N-cadherin and Snail levels in OS cells. On the contrary, exogenous CXCL6 administration enhanced the migration and invasive abilities of OS cells. Moreover, silencing of CXCR1/2 suppressed migration, invasion and EMT of OS cells with or without treatment with exogenous CXCL6. In addition, exogenous CXCL6 promoted the activation of PI3K/AKT and β-catenin signaling pathways, which could be repressed by CXCR2 knockdown. Inactivation of PI3K/AKT or β-catenin pathway by specific inhibitors effectively suppressed CXCL6-induced migration, invasion and EMT of OS cells. Finally, overexpression of CXCL6 significantly contributed to tumor growth, pulmonary metastasis and activation of PI3K/AKT and β-catenin pathways in nude mice in vivo, which were repressed by treatment with CXCR2 antagonist. Our results suggest that CXCL6/CXCR1/2 axis promotes the proliferation and metastasis of OS cells.